'It isn't my area.' Coaches' awareness of concussion protocols in Scottish youth football. Issue 1 (February 2021) - McArdle, David; DeMartini, Anne; Kim, Sungwon; Connaughton, Daniel
Abstract : This paper discusses an externally-funded project into Scottish coaches' awareness of the sports concussion prevention initiative, If in Doubt, Sit Them Out . It explores the short-term risks of concussion to youth participants in particular before analysing the data from interviews with ten coaches of girls' football. The coaches' apparent lack of awareness of the policy are highlighted and the possibility that the different resources in girls' and boys' football, and between girls' performance and girls' recreational participation, might impact on injury recognition and treatment, are explored. The paper highlights the need for further research into those areas, and the need to immediately address the apparently low levels of awareness of If in Doubt . With that in mind, proposals for both immediate and longer-term reform for its dissemination are introduced.